LITERASI DASAR DALAM PENDIDIKAN SD: TANTANGAN DAN UPAYA PERBAIKAN - Ananda, Rizki; Cahyani, Meilana; Herly, Adinda Dwiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study addresses the challenges and improvement efforts in fundamental literacy in elementary schools. Based on the Programme for International Student Assessment (PISA) 2018 report, Indonesia's reading literacy ranked 72nd out of 78 participating countries, indicating a significant need for improvement. Key challenges include limited availability of adequate literacy materials, low family support for reading stimulation, and insufficient teacher training in effective literacy methods. This qualitative study utilizes a literature review approach, using information taken from books, research reports, national journal articles, and pertinent education policy documents that were released between 2019 and 2024. Data analysis involved descriptive-qualitative methods, categorizing information into concepts and scope of basic literacy, implementation issues in elementary schools, and relevant improvement strategies.The results of the study showed that pupils' reading enthusiasm and literacy skills were low., inadequate infrastructure, and limited teacher competence are major obstacles. Strategies such as the School Literacy Movement (GLS), establishment of literacy clubs, reading aloud, and utilization of visual media have shown positive results. Providing adequate facilities and incentives, fostering collaboration among stakeholders, and continuous teacher training are crucial for successful literacy programs. The study concludes that a holistic and sustained approach involving students, teachers, school environments, and educational policies is essential to enhance basic literacy, preparing students for 21st-century educational challenges